Greenjrah integration: From materialism to maslahah in sharia-compliant green investment among generation z Muslims - Ahmad Irkham; Salsabila Aizzatul Muna; Harisalfi Fadhil Mukhlash; Pungky Lela Saputri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Research on Islamic sustainable investing often examines religiosity, environmental concern, and financial self-control separately, leaving limited explanation of how value transformation among young Muslims becomes consistent sharia-compliant green investment behaviour and supports economic resilience. This paper develops GREENJRAH, an integrative pathway linking financial hijrah, green hijrah, and spiritual hijrah, within Indonesia’s Generation Z context. Methods: Using a descriptive qualitative, literature-based design, we synthesise interdisciplinary studies in Islamic behavioural finance, maqasid al-shariah and maslahah ethics, and environmental, social, and governance (ESG) investing to build a conceptual framework. Findings: Financial hijrah strengthens planning, budgeting, and sharia screening discipline; green hijrah increases ecological awareness and preference for responsible assets; spiritual hijrah anchors motives in tawhid, khalifah stewardship, and maqasid orientation, reducing short-termism and speculative impulses. Together, these dimensions can generate measurable behaviour change such as stronger intention to invest, greater allocation to sharia-compliant green instruments (e.g., green sukuk), longer holding horizons, and reduced trend-driven trading. These shifts may strengthen household financial buffers and help mobilise youth capital for low-carbon development. Conclusion: GREENJRAH provides guidance for regulators, Islamic financial institutions, and universities to connect youth spirituality with green finance action through literacy programs and product strategies. Novelty/Originality of this article: The study formulates an explicit tri-dimensional hijrah mechanism that integrates financial discipline, ecological responsibility, and maqasid-oriented spirituality to explain sharia-compliant green investment among Indonesian Generation Z Muslims.